Factors Affecting Prenatal Care in Peruvian Women: Understanding Social and Health Barriers - Poemape Aguirre, Fabricio Hernan (2025)
Introduction: Prenatal care fully monitors and evaluates the pregnant woman and the fetus, detecting early complications during pregnancy. The World Health Organization recommends a minimum of 8 prenatal check-ups; However, there are still pregnant women with inadequate prenatal care coverage. Objective: Identify the sociodemographic and obstetric factors associated with inadequate coverage of prenatal care in Peruvian women. Materials and methods: Cross-sectional study with 18,574 Peruvian women between 15 and 49 years old, participants in the 2022 Demographic and Family Health Survey. A multivariate analysis was performed with logistic regression. Results: Women without a partner (RPa:1.11), without education (RPa:1.44), secondary education (RPa:1.11), not affiliated with public health insurance (RPa:1.12), with ≥5 members in the household (RPa:1.09), who did not plan their pregnancy (RPa:1.09), without early initiation of prenatal care (RPa:2.59), multiparous (RPa:1.09), and severely multiparous (RPa:1.28) had a higher risk of inadequate coverage. of prenatal care. Those residing in rural areas had a lower risk (RPa:0.86); while age was inversely proportional to risk. Conclusion: Some sociodemographic and obstetric factors associated with inadequate prenatal care coverage were identified, the approach of which could help prevent this event.